Red Light-Induced Phosphorylation of Plasma Membrane H+-ATPase in Stomatal Guard Cells. Issue 2 (13th August 2018) - Ando, Eigo; Kinoshita, Toshinori
Abstract : Red light induces photosynthesis-dependent phosphorylation of plasma membrane H + -ATPase in guard cells to promote stomatal opening in whole leaves. Abstract: Stomatal opening is stimulated by red and blue light. Blue light activates plasma membrane (PM) H + -ATPase by phosphorylating its penultimate residue, threonine, via a blue light photoreceptor phototropin-mediated signaling pathway in guard cells. Blue light-activated PM H + -ATPase promotes the accumulation of osmolytes and, thus, the osmotic influx of water into guard cells, driving stomatal opening. Red light-induced stomatal opening is thought to be dependent on photosynthesis in both guard cell chloroplasts and mesophyll cells; however, how red light induces stomatal opening and whether PM H + -ATPase is involved in this process have remained unclear. In this study, we established an immunohistochemical technique to detect the phosphorylation level of PM H + -ATPase in guard cells using whole leaves of Arabidopsis ( Arabidopsis thaliana ) and unexpectedly found that red light induces PM H + -ATPase phosphorylation in whole leaves. Red light-induced PM H + -ATPase phosphorylation in whole leaves was correlated with stomatal opening under red light and was inhibited by the plant hormone abscisic acid. In aha1 - 9, a knockout mutant of one of the major isoforms of PM H + -ATPase in guard cells, red light-dependent stomatal opening was delayed in whole leaves. Furthermore, the photosynthetic electron transport inhibitor 3-(3, 4-dichlorophenyl)-1, 1-dimethylurea inhibited red light-induced PM H + -ATPase phosphorylation as well as red light-induced stomatal opening in whole leaves. Our results indicate that red light-induced PM H + -ATPase phosphorylation in guard cells promotes stomatal opening in whole leaves, providing insight into the photosynthetic regulation of stomatal opening.